UN NUEVO NOTOSTYLOPIDAE (MAMMALIA, NOTOUNGULATA) PROVENIENTE DE LA FORMACION LUMBRERA (GRUPO SALTA) DEL NOROESTE ARGENTINO (Ameghiniana, 2013)
Boreastulops lumbrerensis gen. et sp. nov. is described. All the remains come from the Lumbrera Formation (Early Eocene) at Pampa Grande region (Salta Province). It represents the first unquestionable Notostylopidae outside of Patagonia. Morphologically it is close to Otronia muehlbergi from the Mustersan (Middle Eocene) of Patagonia.